Intelligence Science and Big Data Engineering. Image and Video Data Engineering 5th International Conference, IScIDE 2015, Suzhou, China, June 14-16, 2015, Revised Selected Papers, Part I - He, Xiaofei; Gao, Xinbo; Zhang, Yanning; Zhou, Zhi-Hua; Liu, Zhi-Yong; Fu, Baochuan; Hu, Fuyuan; Zhang, Zhancheng (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2015)
The two-volume set LNCS 9242 + 9243 constitutes the proceedings of the 5th International Conference on Intelligence Science and Big Data Engineering, IScIDE 2015, held in Suzhou, China, in June 2015. The total of 126 papers presented in the proceedings was carefully reviewed and selected from 416 submissions. They deal with big data, neural networks, image processing, computer vision, pattern recognition and graphics, object detection, dimensionality reduction and manifold learning, unsupervised learning and clustering, anomaly detection, semi-supervised learning.